2023
DOI: 10.1155/2023/6620157
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality in Sepsis Patients without Lactate Levels Increasing Early

Abstract: Objectives. Our purpose was to investigate the influencing factors for mortality in sepsis patients without lactate levels increasing in the early stage. Methods. We conducted a retrospective observational study involving 830 adult sepsis patients admitted to ICU. We calculated time-weighted lactate (LacTW), a dynamic value that incorporates both the magnitude of change and the time interval of such change, to represent lactate levels in the first 24 hours. ROC curve was used to find the cutoff of LacTW for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Lactate is an important marker of sepsis, and a delayed increase in lactate levels was reported to be independently associated with in-hospital mortality rate [ 31 ]. However, the lactate levels in the participants of the present study were unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate is an important marker of sepsis, and a delayed increase in lactate levels was reported to be independently associated with in-hospital mortality rate [ 31 ]. However, the lactate levels in the participants of the present study were unknown.…”
Section: Discussionmentioning
confidence: 99%
“…39 Indicators related to organ dysfunction, such as acute physiology and chronic health assessment II (APACHE II) score, APTT, total bilirubin, creatinine, hypotension, chronic kidney disease, and the need for continuous renal replacement therapy (CRRT), are associated with microcirculatory impairment and increased sepsis mortality. 40 Overall, reduced HCT and prolonged APTT are important indicators for predicting the prognosis of sepsis. It is worth noting that inflammation and coagulation often interact in the pathophysiological process of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that lactate clearance serves as a marker for ongoing tissue hypoxia and can predict mortality in patients with severe sepsis [ 13 , 14 ]. Additionally, improving lactate clearance has been associated with better outcomes in patients with sepsis and AKI [ 15 , 16 ]. In the setting of cardiac surgery and extracorporeal life support (ECLS), elevated lactate levels and impaired lactate clearance have been linked to poor outcomes, emphasizing the importance of monitoring lactate dynamics [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%